2013
DOI: 10.1097/brs.0000000000000014
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Pediatric Spine Surgery Using the Vertical Expandable Prosthetic Titanium Rib

Abstract: The complication rate is consistent with that reported in the literature. Correct determination of the levels to be instrumented, preoperative improvement of nutritional status, and better evaluation of the preoperative and postoperative respiratory function are important factors in minimizing the potential complications of a technique that is used in weak patients with complex deformities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 33 publications
0
16
0
2
Order By: Relevance
“…Moreover, the complications inherent to fusionless spinal distraction surgery are frequent. A recently published review of the French VEPTR series reported a high complications rate, comparable to other series [28], although, with experience, recommendations can be made to limit the incidence.…”
Section: Veptrmentioning
confidence: 73%
“…Moreover, the complications inherent to fusionless spinal distraction surgery are frequent. A recently published review of the French VEPTR series reported a high complications rate, comparable to other series [28], although, with experience, recommendations can be made to limit the incidence.…”
Section: Veptrmentioning
confidence: 73%
“…Bess and others [4][5][6][7] showed the complication rate with growing rod treatment to be high; however, several studies have shown that the risk of neurologic injury resulting from growing rod surgery is low, with a reported incidence of 0.4% to 3%. Rib-based distraction surgery has also been shown to have high complication rates but there are few reports in the literature on neurologic injury after rib-based distraction surgery [3,[8][9][10][11]. Rates of neurologic injury have been variable and inconsistently defined, with reported complication rates ranging from 1.8% to 11% [3,12,13].…”
Section: Introductionmentioning
confidence: 92%
“…18 After extubation, incentive spirometry 20 and chest physiotherapy are initiated to optimize pulmonary toileting. In a multicenter retrospective study 22 of 54 children who had VEPTRs implanted, acute respiratory insuffi ciency developed in 3 children in the immediate postoperative period. This fi nding highlights the importance of frequent assessments of respiratory status.…”
Section: Pulmonary Functionmentioning
confidence: 99%
“…Some of the complications are related to the repetitive nature of these expansions, because the original incision is the portal of entry. 5 Potential complications are listed in 31 acute respiratory insuffi ciency immediately postoperatively, 22 and chronic respiratory insuffi ciency due to chest wall stiffness after implantation. 22 Emans et al 18 reported 12 complications in 31 patients, for a rate of 39%.…”
Section: Potential Complicationsmentioning
confidence: 99%
See 1 more Smart Citation